Characteristics of Chloride Transport in Nasal Mucosa from Patients with Primary Ciliary Dyskinesia - Cho, Do-Yeon (2010)
OBJECTIVES: Primary ciliary dyskinesia (PCD) is an inherited disorder that produces lifelong difficulties with chronic airway inflammation. Little is known about the role of chronic airway inflammation on chloride ion transport properties in PCD. This study is to assess the cAMP-regulated chloride (Cl) ion transport properties of freshly excised nasal mucosa from PCD compared with normal and chronic rhinosinusitis (CRS). STUDY DESIGN: Electrophysiology study utilizing Ussing type hemi-chamber technique with three different types of nasal tissue (normal, CRS, PCD) obtained from patients during endoscopic surgery at tertiary referral center. METHODS: Nasal tissues were examined under short-circuit conditions and gradient-driven Cl currents were continuously recorded. The cAMP elevating agonist (forskolin) was added to stimulate CFTR-mediated Cl secretion. To prevent misinterpretation of flux measurement, Cl transport inhibitors were used at the end of all experiments. Basal Cl currents (I(Cl)) and changes in I(Cl)to forskolin (ΔI(Cl)) were compared between normal, CRS and PCD nasal tissues. RESULTS: Forskolin stimulated Cl currents across all different types of nasal epithelia. The Cl secretory response was effectively blocked by the Cl ion transport inhibitors. I(Cl) were significantly higher in normals (155.0 ± 9.3μA/cm(2)) compared to CRS (79.1 ± 15.0μA/cm(2)) and PCD (70.9 ± 20.4μA/cm(2)) (p = 0.005). ΔI(Cl) in CRS (14.8 ± 2.3μA/cm(2)) and PCD (12.2 ± 2.4μA/cm(2)) were markedly diminished compared to normals (28.3 ± 4.7μA/cm(2)) (p = 0.024). CONCLUSIONS: PCD tissues were characterized by impaired I(Cl) and ΔI(Cl). Both parameters were reduced by 54.3 % and 56.9 % in PCD when compared to normals.